The Influence of Corporate Social Responsibility on Company Profitability (Case Study of Banking Companies in Listing in the 2013-2017 Period - Setyani Sri H; Desnia Hardianti (ADVANCE, 2019)
The purpose of this study is to obtain empirical evidence about the significance of the influence of Corporate Social Responsibility on Company Profitability in banking companies listed on the IDX. The results of this study indicate that: 1) Employee Cost is a negative effect that is not significant for profitability. 2) Partnership Costs have a significant negative effect on profitability. 3) Environmental Development Costs have a positive and insignificant effect on profitability and collectively Employee Health Costs, Partnership Costs, and Community Development Costs have a significant and able to explain 8.9% of the profitability variables of the banking company on the IDX.